The smart cyber ecosystem for sustainable development - Kumar, Pardeep, 1976-; Jain, Vishal, 1983-; Ponnusamy, Vasaki, 1974- (Hoboken : Wiley-Scrivener, 2021)
The Cyber Ecosystem can be a replica of our natural ecosystem where different living and non-living things interact with each other to perform specific tasks. Similarly, the different entities of the cyber ecosystem collaborate digitally with each other to revolutionize our lifestyle by creating smart, intelligent, and automated systems/processes. The main actors of the cyber ecosystem, among others, are the Internet of Things (IoT), Artificial Intelligence (AI), and the mechanisms providing cybersecurity. This book documents how this blend of technologies is powering a digital sustainable socio-economic infrastructure which improves our life quality. It offers advanced automation methods fitted with amended business and audits models, universal authentication schemes, transparent governance, and inventive prediction analysis
BIBINDX
Keywords: Artificial intelligence; Internet of things; Computer networks -- Social aspects; Electronic books